Synthesis of pharmaceutical intermediates by toluene benzylation over heteropoly acids on different support - Bokade, Vijay V.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{Selective formation of pharmaceutical intermediates like diphenylmethane, dimethyl-diphenylmethane, benzyl toluene and benzoic acid by liquid phase, toluene benzylation with benzyl chloride as a benzylating agent, was systematically studied over plane clay (K-10, montmorillonite), plane H-Beta, plane MFI structured titanosilicate (TS-1) and heteropoly acids [
Keywords: heteroassembly; nanoplates; polyfunctional capping agents; shape selective synthesis of gold-silver nanostructures; surface confinement